The Role of Reason in Establishing the Objectives of Sharia (Maqasid al-Sharia): A Research and Comparative Study of the Views of Imam Izz al-Din ibn ’Abd al-Salam and Imam al-Shatibi - Muhammed Hanif; Muhammed Sajid Naseem Khan; Muhammad Rafique (Journal of Religion and Society, 2025)
This research article explores the status and scope of human reason (Aql) in understanding and establishing the Higher Objectives of Sharia (Maqasid al-Sharia), through the lenses of two towering figures in Islamic jurisprudence: Imam Izz al-Din ibn 'Abd al-Salam and Imam al-Shatibi. The central premise of this study is that Islamic Sharia is not merely a collection of rigid laws but a logical system designed to secure human interests (Masalih) and repel harms (Mafasid) a system whose profound wisdom is accessible through the faculty of reason. ​The study highlights that Imam Izz al-Din ibn 'Abd al-Salam (the founder of Maqasid thought) perceives reason as the "Scale of Interest" (Mizan al-Maslahah), capable of identifying good and evil even prior to the arrival of revelation. On the other hand, Imam al-Shatibi (the great systematizer of Maqasid) utilizes an Inductive Method (Istiqra) to position reason as the "Servant and Interpreter of Revelation," whose primary task is to derive universal principles from the particular texts of Sharia. The research concludes that both scholars view reason as a "revealer" (Kashif) and "interpreter" of Divine Intent rather than an independent legislator. The findings emphasize that adopting this rational and objective-oriented approach is essential for addressing contemporary complex issues and maintaining the dynamic nature of Islamic Law. ​Keywords: Maqasid al-Sharia, Reason (A ql), Imam Izz al-Din ibn 'Abd al-Salam, Imam al-Shatibi, Maslahah (Public Interest), Inductive Method, Comparative Jurisprudence